PENGEMBANGAN MEDIA PEMBELAJARAN ANIMASI PADA MATERI PENCIPTAAN MANUSIA DALAM AL-QUR’AN UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA - Lestari, Indah Ayu; Nasihin, Muhammad (Jurnal Muara Pendidikan, 2025)
This study aims to develop animated learning media on the topic of human creation in the Qur’an to enhance students’ understanding. The study is grounded in the need for interactive and contextual learning media in the digital era, particularly in Islamic Religious Education at the university level. This research employed a research and development method involving need analysis, design, development, expert validation, product revision, and limited trials. The results indicated that the developed animated learning media demonstrated excellent feasibility based on evaluation by content and media experts. Limited trials revealed improved student understanding and positive responses regarding visual presentation, clarity of narration, and ease of comprehension. In conclusion, the animated learning media is considered feasible and effective as an innovative technology-based tool for teaching Islamic Religious Education in higher education.